2006
DOI: 10.1111/j.1538-7836.2006.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute activation of the endothelium results in increased levels of active von Willebrand factor in hemolysis, elevated liver enzymes and low platelets (HELLP) syndrome

Abstract: To cite this article: Hulstein JJJ, van Runnard Heimel PJ, Franx A, Lenting PJ, Bruinse HW, Silence K, de Groot PhG, Fijnheer R. Acute activation of the endothelium results in increased levels of active von Willebrand factor in hemolysis, elevated liver enzymes and low platelets (HELLP) syndrome. 2006; 4: 2569-75. Summary. Background: HELLP (hemolysis, elevated liver enzymes and low platelets) syndrome is a severe complication of pre-eclampsia in pregnancy, characterized by microvascular platelet thrombi. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 19 publications
6
77
0
4
Order By: Relevance
“…Lower levels are found in new-borns and in older people, and in the second and third trimester of normal pregnancies [36,37]. Alpoim and colleagues found decreased ADAMTS13 levels in preeclamptic women compared to normotensive pregnant women [38], while in other studies a significant ADAMTS13 reduction was limited to the rarer pregnancy complication HELLP syndrome (Haemolysis Elevated Liver enzymes, Low Platelets) [39]. Others again have found normal ADAMTS13 levels but increased VWF in preeclampsia [40].…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels are found in new-borns and in older people, and in the second and third trimester of normal pregnancies [36,37]. Alpoim and colleagues found decreased ADAMTS13 levels in preeclamptic women compared to normotensive pregnant women [38], while in other studies a significant ADAMTS13 reduction was limited to the rarer pregnancy complication HELLP syndrome (Haemolysis Elevated Liver enzymes, Low Platelets) [39]. Others again have found normal ADAMTS13 levels but increased VWF in preeclampsia [40].…”
Section: Discussionmentioning
confidence: 99%
“…First, it may be a consequence of the feminine predominance of TTP (being itself at least partially linked to the feminine predominance classically observed in any disease with an autoimmune background); furthermore, most women with TTP (between 60 and 70%) are child-bearing age women [1,2]. Second, pregnancy is associated with physiological coagulation changes predisposing to hypercoagulability and particularly to a dysbalance of the VWF/ADAMTS13 system: indeed, during the course of pregnancy, VWF levels in plasma increase progressively to reach levels 2.5-3 fold higher levels at term (with peak values occurring immediately following delivery) while ADAMTS13 decreases progressively (ADAMTS13 activity decreases of about 30% at term when compared to baseline levels before pregnancy) (Supplementary Table 1) [16][17][18][19][20][21][22][23]. The physiological decrease of ADAMTS13 during pregnancy may be due either to a consumption mechanism by its VWF substrate [16], or to a direct effect of hormonal substances on ADAMTS13 metabolism [24].…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…Indeed, puerperium and post-partum TTP are more rare than ante-partum TTP and they usually occur following a late 3 rd trimester delivery (about 38 WG) and a median 4 th day postpartum (range 0-42 days) [9]. Third, several studies led in women with pregnancy-associated TMA showed that a severe ADAMTS13 deficiency (activity <10%) was specific for TTP: indeed, only normal or partially deficient ADAMTS13 levels (usually >20%) have been described in either PE, HELLP syndrome or HUS (Supplementary Table 4) [17,19,[21][22][23]. ADAMTS13 activity measurement remains however unavailable in emergency as a routine assay and it may not be useful to argue for a TTP diagnosis at presentation in emergency.…”
Section: Diagnosis Of Ttp During Pregnancymentioning
confidence: 99%
“…Preeclampsia and HELLP are much more common than acute TTP. Patients with HELLP syndrome have normal or moderately decreased ADAMTS13 activity but show increased VWF levels, a high VWF propeptide/VWF antigen ratio (suggestive of endothelial stimulation/damage) and an increased binding affinity of the VWF A1 domain to platelet glycoprotein Ib resembling the situation with the unusually large VWF multimers in severely ADAMTS13 deficient TTP (20). In (severe) preeclampsia the antiangiogenic factors, fms-like tyrosine kinase 1 (sFlt-1), an antagonist of vascular endothelial growth factor (VEGF) and endoglin, an inhibitor of transforming growth factor β (TGF-β) are released from the hypoperfused, hypoxic placenta and elevated in plasma (4).…”
Section: Brief Overview Of Thrombotic Microangiopathies (Tmas)mentioning
confidence: 99%